LOAD FORECASTING METHOD WITH DKL 3.01 - Qoriatul Fitriyah (Politeknik Manufaktur Astra, 2011)
DKL 3.01 methods is using econometric approach combined with data analysis of electricity sales and economic growth which is represented by Product Domestic Regional Brutto (PDRB).